2017
DOI: 10.1021/acs.jpca.7b01509
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Methane to Methanol over Single Site Palladium Oxide Species on Silica: A Mechanistic view from DFT

Abstract: Abstract:A theoretical analysis was carried out on the mechanism of methane oxidation to methanol occurring on single site palladium oxide species [PdO] 2+ supported on a model of Al-MCM-41 silica. Both 6 and 8-membered ring structures were considered to represent the support.The energy profile for each elementary reaction was determined from density functional theory calculations with the OPBE functional. The calculated overall activation energies are close to the experimental values. Our calculations confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Its additional charge transfer character is also evident based on the intense pink-purple color of the complex upon CO adsorption ( Fig S5). Previous studies claimed the formation of Pd(IV) cation on various solid supports and zeolites based on (1) the indirect evidence from stoichiometry from XRD refinement 27 (2) DFT-modeling 46 and (3) the presence of the high binding energy feature (relative to PdO with BE of Pd 3d5/2 at 336.5-337.0 eV) in the Pd 3d XPS spectra 24,28,29,47,48 . Interestingly, in some works a feature at 337.7-338.0 eV on ceria supports, for example, 49,50,51 [8][9][10] We also note that upon dehydration either in He or O2, the color of the sample changes from light yellow to light pink (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its additional charge transfer character is also evident based on the intense pink-purple color of the complex upon CO adsorption ( Fig S5). Previous studies claimed the formation of Pd(IV) cation on various solid supports and zeolites based on (1) the indirect evidence from stoichiometry from XRD refinement 27 (2) DFT-modeling 46 and (3) the presence of the high binding energy feature (relative to PdO with BE of Pd 3d5/2 at 336.5-337.0 eV) in the Pd 3d XPS spectra 24,28,29,47,48 . Interestingly, in some works a feature at 337.7-338.0 eV on ceria supports, for example, 49,50,51 [8][9][10] We also note that upon dehydration either in He or O2, the color of the sample changes from light yellow to light pink (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore we have also investigated the direct conversion of methane to ethanol by PdO/Al-MCM-41 and found that the [Pd=O] 2+ species supported on a 8-membered ring was more reactive than those supported on a 6-membered ring. 18 For this reason, we limit ourselves in the present work to location of the Pd 2+ cation on a 8-membered ring. We have represented the surface of acid silica-alumina using structures of silsesquioxane type that simulate the 8 membered rings in which two Si atoms were substituted by two Al atoms ((H 18 Al 2 Si 14 O 24 ), see Figure S1).…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…15 Those experimental works were also strongly supported by theoretical studies of CH 4 oxidation, mainly by means of Density Functional Theory (DFT). 15,18,19 In particular, the pivotal role of the acid sites was evidenced for the activation of CH 4…”
Section: Introductionmentioning
confidence: 99%
“…Its additional charge transfer character is also evident based on the intense pink-purple color of the complex upon CO adsorption ( Fig S5). Previous studies claimed the formation of Pd(IV) cation on various solid supports and zeolites based on (1) the indirect evidence from stoichiometry from XRD refinement 27 (2) DFT-modeling 46 and (3) the presence of the high binding energy feature (relative to PdO with BE of Pd 3d5/2 at 336.5-337.0 eV) in the Pd 3d XPS spectra 24,28,29,47,48 . Interestingly, in some works a feature at 337.7-338.0 eV on ceria supports, for example, 49,50,51 was attributed to Pd(IV) ions or PdO2 .…”
Section: Resultsmentioning
confidence: 99%